Functional and Biological Properties of Sang Yod Rice Bran Hydrolysate Prepared by enzymatic Hydrolysis and Its Application in Rice Pudding Product - Natcha Phantuwong (Prince of Songkla University, 2019)
Thesis (Ph.D., Functional Food and Nutrition)--Prince of Songkla University, 2017